Clinical Diversity of Multiple Myeloma at the First Presentation through the Time Lapse to Diagnosis in Kurdistan Region, Iraq - Truska A. Amin (Zanco Journal of Pure and Applied Sciences, 2020)
Multiple myeloma (MM) is a malignancy of the plasma cells. The study aimed to know the clinical diversity of MM at presentation, the time lapse from the first symptoms to diagnosis, and the association of this time lapse with the International Staging System (ISS) of MM. This is a retrospective observational study that was performed on 176 patients who had MM and were admitted to Hiwa Hospital in Sulaimani, Nanakaly Hospital in Hawler, and Azadi Hematology - Oncology Center in Duhok, from October 2010 to December 2019. Demographic and detailed clinical features were recorded, and the ISS of MM was used to assess possible effects of time lapse on patients’ outcomes. The mean ± SD (standard deviation) of patients’ age was 60.58 ± 11.54 years, and the majority of the patients (52.27%) were from Sulaimani. Most of them had an O+ blood group and a body mass index (BMI) of more than normal (30.68%, and 63.63%, respectively). Most of the patients had bone pain, ≥2 lytic lesions, hypocalcemia and hypercalcemia, and renal impairment and stage II and III of ISS of MM at the time of diagnosis (78.98%, 32.39%, 49.43%, 89.77%, and 75.1%, respectively). Furthermore, their mean ± SD of time lapse from the first symptom to diagnosis was 3.01 ± 3.18 months, and its association with ISS was none significant. The clinical features of MM at diagnosis are mostly nonspecific, and may be shared by a wide range of clinical conditions. However, patients who have fatigue, bone pain, renal impairment, pallor, and infective events should arouse the clinical suspicion of MM.